A Numerical Study of the Effect of Endwall Injection Blowing Ratio on a High Pressure Turbine Cascade Performance - Atef Alameldin; Mohamed El-Ghandour; Yasser Kamal (Port Said Engineering Research Journal, 2019)
The aerodynamics of the flow in a turbine stage is complex and still the subject of many ongoing researches. The secondary flow is the major source of aerodynamic losses in a turbine stage. Fluid injection from the endwall is used to improve the aerodynamic performance. For the current study, the change of injection blowing ratio has been investigated as an effective way to increase turbine efficiency by mitigating the strength of vortices. The interaction between the main flow and the injection flow from flat endwall is analyzed by numerical simulation. Five endwall injection holes were placed near the blade suction side on a typical flat blade cascade with two injection blowing ratios. In these cases, each hole has the same blowing ratio. Furthermore, two other test cases (mixing blowing ratio) in which every hole has its own blowing ratio independent of other holes. The new injection arrangements techniques have proved its effectiveness in increasing blade loading by 1.85 % more than baseline test case blade loading. In addition to suppression flow losses by 2.1 % less than baseline test case losses.